2013
DOI: 10.1021/jo4012915
|View full text |Cite
|
Sign up to set email alerts
|

Four Mechanisms in the Reactions of 3-Aminopyrrole with 1,3,5-Triazines: Inverse Electron Demand Diels–Alder Cycloadditions vs SNAr Reactions via Uncatalyzed and Acid-Catalyzed Pathways

Abstract: Reaction of 3-aminopyrrole with seven 1,3,5-triazines was studied in a one-step reaction (in situ formation of 3-aminopyrrole) and a two-step reaction (using the tetraphenylborate salt and an amine base). An inverse-electron demand Diels-Alder reaction (IEDDA) was observed with R1 = CF3, CO2Et, and H with the formation of 5H-pyrrolo[3,2-d]pyrimidine derivatives. S(N)Ar was observed when 2,4,6-trifluoro- or 2,4,6-trichloro-1,3,5-triazine were used--1,3,5-triazines that had leaving groups. If excess 1,3,5-triazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 103 publications
0
15
0
Order By: Relevance
“…Moreover, these authors got furo[2,3‐ d ]pyrimidines 109a , b by reaction of 107a with the corresponding 5‐substituted 2‐amino‐ or 2‐ N ‐Boc‐aminofurans . Similarly, the reaction with 1‐substituted 2‐aminopyrroles gave the pyrrolo[2,3‐ d ]pyrimidines 110 , while with 3‐aminopyrrole (generated from 3‐nitropyrrole) pyrrolo[3,2‐ d ]pyrimidine 111 was obtained . Furthermore, the reaction of 107a with 2‐aminoindoles lead to 9 H ‐pyrimido[4,5‐ b ]indoles 112…”
Section: Fluorine‐containing 13‐dienesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these authors got furo[2,3‐ d ]pyrimidines 109a , b by reaction of 107a with the corresponding 5‐substituted 2‐amino‐ or 2‐ N ‐Boc‐aminofurans . Similarly, the reaction with 1‐substituted 2‐aminopyrroles gave the pyrrolo[2,3‐ d ]pyrimidines 110 , while with 3‐aminopyrrole (generated from 3‐nitropyrrole) pyrrolo[3,2‐ d ]pyrimidine 111 was obtained . Furthermore, the reaction of 107a with 2‐aminoindoles lead to 9 H ‐pyrimido[4,5‐ b ]indoles 112…”
Section: Fluorine‐containing 13‐dienesmentioning
confidence: 99%
“…Fused heterocycles 108 – 112 obtained by IEDDA reactions of triazines 107a , b with corresponding aminoazoles …”
Section: Fluorine‐containing 13‐dienesmentioning
confidence: 99%
“…Subsequent elimination generates the product and compound 8 . In a follow‐up study, it was found that the addition of an acid to the mixture slightly increases the yield . This is likely due to protonation of the triazine, which makes it more electrophilic.…”
Section: Mechanistic Studies Of the Iedda Reactionmentioning
confidence: 99%
“…18 S N Ar reactions of 2,4,6-trihalo-1,3,5-triazines have also been found to be acid catalyzed. 17 In this study it was found that acid catalysis was important with chloropyrimidines (5-7); derivatives that only have one activating group present on the pyrimidine ring plus the leaving group. Acid catalysis was not a factor when two (4, 8 and 9) or three (3) activating groups were present on the pyrimidine ring.…”
Section: Introductionmentioning
confidence: 94%
“…Cycloaddition of 3-aminopyrrole (2) with 1,3,5-triazine has been found to be acid catalyzed. 17 This was attributed to a lowering of the LUMO-HOMO interaction that made cycloadditon easier. 18 S N Ar reactions of 2,4,6-trihalo-1,3,5-triazines have also been found to be acid catalyzed.…”
Section: Introductionmentioning
confidence: 99%